ANALISIS PERBEDAAN HARGA SAHAM, RETURN SAHAM, DAN ABNORMAL RETURN SEBELUM DAN SESUDAH STOCK SPLIT PADA PERUSAHAAN HIGH PROFILE DAN LOW PROFILE YANG TERDAFTAR DI BURSA EFEK INDONESIA - Rahmawati, Pita; Nusantoro, Jawoto; Sari, Gustin Padwa (Jurnal Fokus Manajemen Bisnis, 2021)
This research aims to determine whether there are differences in stock prices, stock returns and abnormal returns before and after a stock split in high profile and low profile companies. The research period used in this study was on 2016-2018. The research was analyzed in quantitative method by using a purposive sampling method. Based on the sampling criteria, 40 companies were selected as research samples. Kolmogorov Smirnov One Sample test was used for the normality test. After the normality test was carried out, the data was processed using the two paired-sample difference test. The t-test (paired sample t-test) was used if data were normally distributed but if it was not normally distributed the Wilcoxon Signed Rank test would be used. Hypothesis testing results showed that (1) there are differences in stock prices whether before and after a stock split in high profile companies (2) there are differences in stock prices whether before and after the stock split in low profile companies (3) there are differences in stock returns whether before and after a stock split in the company high profile (4) there is no difference in stock returns whether before and after the stock split in low profile companies (5) there is no difference in abnormal returns whether before and after the stock split in high profile companies (6) there is no difference in abnormal returns whether before and after the stock split in low profile companies (7) there are differences in stock prices after a stock split in high profile companies and low profile (8) there is no difference in stock returns whether before and after the stock split in high profile and low profile companies (9) there is no difference in abnormal stock returns whether before and after a stock split at high profile and low profile companies.